The Influence of Guided Inquiry Learning Strategies and Learning Motivation on the Outcomes of Islamic Education Learning in SMP Negeri 2 Bireuen - Tien Rafida; Evi Idayani (Budapest International Research and Critics University, 2021)
The purpose of this research was to determine: (1) the effect of the implementation of guided inquiry learning strategies on the learning outcomes of Islamic Religious Education, (2) the effect of learning motivation on learning outcomes of Islamic Religious Education, and (3) the interaction of learning strategies and learning motivation on learning outcomes of education. Islam. The research was conducted at SMP Negeri 2 Bireuen. This type of research is a quasi experiment. The study population was all students of class VIII spread over 6 classes. The sampling technique used was cluster random sampling. The data collection instruments were questionnaires and tests. The data analysis technique used was two-way analysis of variance in the α = 0.05 test. The results showed: (1) there was an effect of the implementation of guided inquiry learning strategies on student learning outcomes of Islamic Religious Education. In this case the learning outcomes of students who are taught with guided inquiry learning strategies are higher than the learning outcomes of Islamic Religious Education students taught with expository strategies. (2) there is an influence of learning motivation on students' learning outcomes of Islamic Religious Education, in this case the learning outcomes of students with high learning motivation are higher than the learning outcomes of Islamic Religious Education students with low motivation, and (3) there is an interaction between learning strategies and motivation. learning about student learning outcomes of Islamic Religious Education.